Validation of the Thai version of the family reported outcome measure (FROM-16)© to assess the impact of disease on the partner or family members of patients with cancer - Chantarasap, Pattariya (Health Qual Life Outcomes, 2019)
BACKGROUND: Cancer not only impairs a patient’s physical and psychosocial functional behaviour, but also contributes to negative impact on family members’ health related quality of life. Currently, there is an absence of a relevant tool in Thai with which to measure such impact. The aim of this study was to translate and validate the Family Reported Outcome Measure (FROM-16) in Thai cancer patients’ family members. METHODS: Thai version of FROM-16 was generated by interactive forward-backward translation process following standard guidelines. This was tested for psychometric properties including reliability and validity, namely content validity, concurrent validity, known group validity, internal consistency, exploratory and confirmatory factor analysis. Construct validity was examined by comparing the Thai FROM-16 version with the WHOQOL-BREF-THAI. RESULTS: The internal consistency reliability was strong (Cronbach’s alpha = 0.86). A Negative moderate correlation between the Thai FROM-16 and WHOQOL-BREF-THAI was observed (r = − 0.4545, p < 0.00), and known group validity was proved by a statistically significant higher score in family members with high burden of care and insufficient income. The factor analysis supported both 3-factor and 2-factor loading model with slight difference when compared with the original version. CONCLUSIONS: The Thai FROM-16 showed good reliability and validity in Thai family members of patients with cancer. A slight difference in factor analysis results compared to the original version could be due to cross-culture application.